MODERN TRENDS IN PERFECTION OF DIETOTHERAPY IN CHILDREN WITH VIRAL DIARRHEA - L.N. Mazankova; L.I. Kafarskaya; G.Yu. Yakovleva; B.A. Efimov ("Paediatrician" Publishers LLC, 2010)
Authors studied peculiarities of specific composition of bifidus bacteria in infants (n = 32) with viral diarrhea and effectiveness of prebiotic product Immunofortis (formula ?Nutrilon Comfort?) in treatment of prebiotic disorders. Analysis of copro filtrate in acute period of viral diarrhea showed decrease of bifidus bacteria concentration and change of specific composition of intestinal micro flora. Bifidum bacteria B. catenulatum and B. adolescentis were detected in intestinal micro flora though it is not common in children. Dietotherapy with prebiotic formula resulted in restoration of age-specific parameters of specific composition of bacteria (B. bifidum, B. longum) and increase of secretory IgA concentration in coprofiltrate. Authors made a conclusion that Immunofortis has immunobiological effect in children with acute diarrhea.Key words: children, viral diarrhea, bifidus bacteria, nutrition, Immunofortis.(Voprosy sovremennoi pediatrii - Current Pediatrics. - 2010;9(3):107-112)